A Comparative Study of Image Demosaicing - Kaur, Gurpreet; Kaur, Jaskaranjit (International Journal of Computer Sciences and Engineering, 2025)
Digital cameras captures image by using a single image sensor overlaid with a Colour Filter Array (CFA), so image demosaicing is applied to render these images into a viewable format. Image demosaicing is the technique of digital image processing that reconstructs missing color pixels using incomplete color samples. Today Image Demosaicing becomes a major area of research. Bayer Pattern CFA which can be expressed as square matrices is most familiar among the various CFA patterns. The methods of recovering full-color images from a CFA-based detector are commonly referred as colour interpolation or colour demosaicing algorithms. In this paper, we have critically analyzed various demosaicing algorithms and also covered its basic methods and various common demosaicing artifacts.